Determinants of debt behavior. A quantitative study among generation Y individuals in Tashkent, Uzbekistan - Jamilakhon, Kholmatova; Singh, Jugindar Singh Kartar; Subramaniam, Anusuiya; Suppramaniam, Subaashnii (Mattingley Publishing, 2020)
The aim of this paper was to examine the determinants of debt behavior by generation Y. Despite various studies done on savings and debt behavior of students, the relationship between financial education, debt attitude, peer influence and power prestige towards debt behavior among generation Y in Uzbekistan is still unclear. There is a dearth of studies relating to the debt behavior of generation Y individuals in Uzbekistan. This quantitative research collected primary data using self-administered questionnaires, which were sent to generation Yindividuals in Uzbekistan. Data collected from 107 respondents was analyzed using SPSS statistical tool. Based on multiple regression analysis, it was found that only power prestige had a significant impact on debt behavior of generation Y individuals. Financial education, debt attitude and peer influence did not show a significant influence on debt behavior. The findings shed further light on the role of financial education, attitude, peer influence and power prestige in debt behavior. The information provided by this research can help authorities to develop measures to address the rising level of debt. This is the first study of its kind to examine debt behavior among Generation Y individuals in Uzbekistan.